Foliculitis Decalvans In Siblings - D′Souza Mariette; Thadeus Joseph; Ratnakar Chaganti (Wolters Kluwer Medknow Publications, 1997)
Folliculitis decalvans is a rare cause of cicatricial alopecia. Apart from a single report by Shitara and co-workers, familial occurrence of folliculitis decalvans has not been reported. Two families in each of which two siblings were affected with folliculitis decalvans are reported and the aetiologic aspects discussed.